Criminal Law Policy Against Actor Of Criminal Performance Persecution - Muhammad Adiel Aristo (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
In simple terms, it can be described that the act of persecution starts with the act of identifying, searching for and executing the perpetrators who are suspected of committing criminal acts based on the above reasons, or in other words, that persecution is an act of judgment without going through the proper process or procedure, which in criminal law called the act of vigilante (eigenrechting). The formulation of the problem presented is how is the criminal law policy towards the perpetrators of criminal acts of persecution. The method of approach in research uses normative juridical research specifications in the form of analytical descriptive. Data consists of secondary data obtained from literature or document studies. Based on the research, it can be concluded that for certain conditions, in the act of vigilantism, especially in the case of self-defense / property / honor, justification reasons can be used, because it meets the elements mentioned in the Criminal Code provisions, especially Article 49 of the Criminal Code. Unlike the case with the act of persecution, in the act of persecution there are no elements that can be used as justification and excuse for forgiveness in their actions, because when viewed from the process, the act of persecution, begins with finding,Keywords: Criminal Law Policy; Perpetrators; Criminal Acts of Execution.